Improvement of post-hypoxic action myoclonus with levetiracetam add-on therapy: A case report - Božić, Ksenija; Gebauer-Bukurov, Ksenija; Sakalaš, Lorand; Divjak, Ivana; Ješić, Aleksandar (Vojnosanitetski pregled, 2014)
Introduction. Chronic post-anoxic myoclonus, also known as Lance-Adams syndrome, may develop following hypoxic brain injury, and is resistant to pharmacological therapy. Case report. The patient we presented developed post-anoxic action myoclonus with severe, completely incapacitating myoclonic jerks. Myoclonus did not respond to the treatment with commonly used agents, i.e. valproate and clonazepam alone or in combination. Improvement of the action myoclonus was observed only after adding levetiracetam. Conclusion. Although Lance-Adams syndrome may not be fully curable at this point, levetiracetam appears to be a promising agent that can significantly improve functional level and overall quality of life of patients with this disorder.